PERBANDINGAN KINERJA KEUANGAN PT. BANK SYARIAH INDONESIA, Tbk (BSI) SEBELUM DAN SESUDAH DI MERGER - Cici Widya Prasetyandari (Sekolah Tinggi Ekonomi Islam Al-Furqon Prabumulih, 2022)
This study aims to determine the differences in the financial performance of PT. Bank Syariah Indonesia, Tbk (BSI) Before and after the merger. The population comes from the financial statements of PT. BRI Syariah Bank, PT. Bank Syariah Mandiri, PT. BNI Syariah Bank and PT. Bank Syariah Indonesia, Tbk. The sample used is the financial statements of quarters 1-4 for the 2018-2022 period. The research method used is the Mann Whitney test. The results of data analysis showed that the financial performance of BSI before and after the merger had a significant difference.